THE EVOLUTION OF THE MAIN MACROECONOMIC INDICATORS OF THE ROMANIAN ECOMONY - Caruntu Andreea Laura (Analele Universităţii Constantin Brâncuşi din Târgu Jiu : Seria Economie, 2013)
The economic and financial crisis from the last years continues to affect the economies of many countries at global level. The Gross Domestic Product of these countries has known a serious decline. Romania is one of the countries that try to redress from the decline of the last years. The measures taken in order to make the economy grow have proven to be ineffective in the fight with the recession. This has led to the bankruptcy of many companies, employees being laid off and the level of direct investments has decreased. The paper aims to analyze how has evolved the economy through the analysis of the contribution of direct taxes in the composition of the general consolidated budget, of the evolution of the economic growth, of the evolution of the gross domestic product. The results will show the image of how the economy works. The weight of private companies in the gross domestic product is of 70%, which shows the importance of this sector in the economy.